2009
DOI: 10.1111/j.1365-2982.2009.01301.x
|View full text |Cite
|
Sign up to set email alerts
|

Combined oesophageal impedance‐pH monitoring in preterm newborn: comparison of two options for layout analysis

Abstract: Gastro-oesophageal reflux (GOR) is common in preterm infants. Combined multichannel intraluminal impedance and pH monitoring (pH-MII) is emerging as an useful tool to study both acid and non-acid GOR in this population. We aimed to highlight main advantages and limits of pH-MII in preterm infants and to test whether the inclusion of GOR episodes detected only by pH monitoring details better the features of GOR. Fifty-two symptomatic preterm infants underwent a 24-hour, continuous and simultaneous measurement o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 18 publications
4
27
0
3
Order By: Relevance
“…The relationship between AOP and gastroesophageal reflux (GER) is still controversial [2,3,4]: in a previous study, we have shown that the proportion of apneas triggered by GER is highly variable among preterm infants [4], while other studies have failed to show a causal relationship between the two events [2]. In our experience, non-acid GER appears to be a more effective trigger for apnea than acid GER [5]; it occurs mainly soon after feeding [6], and is often associated with breathing irregularities [7]. …”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…The relationship between AOP and gastroesophageal reflux (GER) is still controversial [2,3,4]: in a previous study, we have shown that the proportion of apneas triggered by GER is highly variable among preterm infants [4], while other studies have failed to show a causal relationship between the two events [2]. In our experience, non-acid GER appears to be a more effective trigger for apnea than acid GER [5]; it occurs mainly soon after feeding [6], and is often associated with breathing irregularities [7]. …”
Section: Introductionmentioning
confidence: 88%
“…Combined multichannel intraluminal impedance and pH monitoring (pH-MII; Sandhill Scientific, Inc., Highland Ranch, Colo., USA) and PSG (System Plus; Micromed, Mogliano Veneto, Italy) were performed as previously described [6]. The clocks of the two instruments were synchronized at minute-second before starting each recording, and the recording of the two layouts was started simultaneously.…”
Section: Methodsmentioning
confidence: 99%
“…In the last decade, combined esophageal impedance-pH monitoring is the most widely used method for the identification of acid and non-acid reflux [8,10,13,14,20,21]. However, this technology does not detect a substantial part of the acid events in premature infants [14,22].…”
Section: Discussionmentioning
confidence: 99%
“…pH-MII was performed as previously described. 13 The single use, flexible pH-MII probe (Comfortec; pH-MII Sandhill Scientific) contains seven impedance rings, which constitute six dipolar impedance channels and one antimony electrode for pH detection, located in the middle of the distal impedance dipole. The distance between each of the impedance rings is 1.5 cm, except for the distance between the two distal ones, which is 2 cm.…”
Section: Methodsmentioning
confidence: 99%
“…13 For this reason, our first hypothesis was that sodium alginate could act mainly by lowering non-acid GER indexes. However, we found that in preterm infants the efficacy of sodium alginate in treating GER is mainly related to the decrease in acid GER indexes, which suggests that the alginate preparation remains inside the stomach for a quite long period after feeding.…”
mentioning
confidence: 99%